Energía Solar en Ecuador: Desafíos y Oportunidades en Edificaciones Comerciales y Públicas - Cevallos Villamarín, Max Erick (2024)
The objective of this study is to evaluate the feasibility of implementing photovoltaic systems in the public and commercial sectors of Ecuador. The methodology is organized into several stages, beginning with an analysis of the current state and regulatory and normative study. This is followed by a technical study, financial study, and finally, an analysis of the results. Information is gathered on the subject of electricity rates in both sectors, current regulations, available technologies, and prices from photovoltaic system suppliers. The financial analysis considers the costs and public policies that support the adoption of this technology, evaluating different voltage levels (low, medium, and high) according to the type of demand, whether with or without hourly demand, using indicators such as net present value (NPV), internal rate of return (IRR), return on investment (ROI), and levelized cost of energy (LCOE). The results indicate that the initial investment is not fully recovered during the project's useful life, which presents a challenge. Accessible financing mechanisms are required to make the adoption of this technology viable. However, photovoltaic systems offer significant potential to reduce energy costs and greenhouse gas emissions, contributing to sustainability. Keywords: solar energy, Ecuador, commercial sector, public sector, financial feasibility, economic analysis, sustainability.